Twelve-tone technique and procedural poetics - Ferry, Mae, author; Steensen, Sasha, advisor; Cooperman, Matthew, committee member (Colorado State University. Libraries, 2025)
Poetry and music have a deeply connected history, beginning with the Ancient Greek performance tradition and continuing with poets such as Susan Howe reading to an experimental jazz soundtrack. In contemporary poetry, these musical influences are often subsumed by the teaching and art of poetry to the point of roteness; rhythm is barely considered, despite its ubiquity, and poetry as an audible performance is further and further distanced from the public ear. To combat this contemporary distance between music and poetry, the author conducted the following poetic experiment: can music be used as a generative source for poetry?
Keywords: music; poetry; music theory